Abdominal scar endometriosis: A case report and review of literature - Vijayan Sharmila; Vandana Kamatham; Arundhathi Shankaralingappa (Indian Journal of Pathology and Microbiology, 2023)
Endometriosis is defined as the presence of functioning endometrial tissue outside the uterine cavity. Abdominal wall or cutaneous endometriomas are quite uncommon with an incidence of less than 1%. Abdominal wall endometrioma can occur in a previous surgical scar, commonly following obstetrical and gynecological surgeries. Cutaneous endometriosis is difficult to diagnose because of its nonspecific symptoms and is often confused with other dermatological and surgical diseases thereby delaying the diagnosis and management. We are reporting a case of scar endometriosis at the site of previous cesarean scar involving the rectus sheath. The pathogenesis, diagnosis, and treatment of this rare condition are being discussed. Awareness of the clinical features and presentation of this rare condition is essential for timely diagnosis and management.